Experimental Investigation of Mixing Performance in Laser-fabricated Microfluidic Micromixers - Fahizan, Mahmud (Universiti Malaysia Sarawak (UNIMAS), 2021)
Microfluidic mixing is a key process in miniaturized analytical system. Achieving adequate mixing performance is considerably difficult in micromixer as the flow is always associated with unfavourable laminar flow. The mixing performance of these micromixers are generally characterized as a function of mixing index based on dispersion (homogeneity) information, leading to either overestimated or underestimated mixing index. This research presents a novel method to determine mixing index of micromixers based on red, green and blue (RGB) colour model by decoding mixing images to their respective red, green and blue pixel intensities. The proposed method is foreseen handy and robust in characterizing mixing in real time for gradient mixing in networked microchannels and multivortex mixing for the manipulation of fluids, particles and biological substances. Several digital composite images were used to perform initial benchmarking, and the proposed method accurately quantified the mixing index significantly better than previously adopted methods. T-, Y-, and Dean micromixer were laser fabricated and the proposed Dean micromixer exhibits higher mixing performance (about 27% better) as compared to T- and Y- micromixers for 40 ≤ Re ≤ 100. Extraneously induced ultrasound and thermal energy were studied and their effects towards mixing performance is more significant at 5 ≤ Re ≤ 20 because of prolonged mechanical effect within the system. It is also found that the mixing index increases of about 6% to 10% at various Reynolds number once the sonicated mixing fluids were heated from 30 °C to 60 °C. The proposed method and improved design of the Dean micromixer are potentially useful for sensitive microfluidic devices as direct contact of the inductive energy sources may cause unwanted substrate damage and structural deformation especially for applications in biological analysis and chemical synthesis.